CRUST-MANTLE STRUCTURES AND GOLD ENRICHMENT MECHANISM OF MANTLE FLUID SYSTEM - Deng J.; Wang Q.; Wei Y.; Sun Z. (My University, 2003)
Gold enrichment mechanism of ore-forming fluid is the essence of gold metallization. This paper summarizes the distinguishing symbols of mantle fluid and effect of crust-mantle structure on fluid movement. Fluid moving processes include osmosis, surge, gas-liquid alternation and mutation of fluid speed. During fluid movement, gold will be enriched gradually. Finally, a layered circulatory system is illustrated in this paper.